Ceruloplasmin, a moonlighting protein in fish. Issue 82 (November 2018) - Das, Sweta; Sahoo, Pramoda Kumar
Abstract: Ceruloplasmin is an ancient multicopper oxidase evolved to insure a safe handling of oxygen in some metabolic pathways of vertebrates. The current knowledge of its structure provides a glimpse of its plasticity, revealing a multitude of binding sites that point to an elaborate mechanism of multifunctional activity. Ceruloplasmin is highly conserved throughout the vertebrate evolution. Cupredoxin, a multi-cupper blue protein is believed to be the evolutionary precursor of ceruloplasmin with three trinuclear and three mononuclear copper binding sites. There are 20 copper-binding residues in ceruloplasmin gene out of which 16 residues are conserved in fish. This ceruloplasmin gene is being characterized in zebrafish ( Danio rerio ), rohu ( Labeo rohita ), Indian medaka ( Oryzias melastigama ), catfish ( Ictalurus punctatus ), icefish ( Chionodraco rastrospinosus ), goldfish ( Carassius auratus ) and yellow perch ( Perca flaviscens ). The complete coding sequence of fish ceruloplasmin gene is around 3.2 kb which codes for 1000 to 1100 amino acid residues. The size of ceruloplasmin gene sequence in fish ranges around 13 kb containing 20 exons and 19 introns. Liver is the major site of synthesis in fish. Increased expression of this gene during bacterial infection in channel catfish and rohu suggested its potential involvement in bacterial disease response in fish. It has been found to serve as an indirect marker for selection against Aeromonas hydrophila resistance in rohu carp. Ceruloplasmin expression is also evident during parasitic infection in few fish species. The role of this gene is well studied during inflammatory response to hormonal, drug and heavy metal mediated toxicity in fish. Overall, ceruloplasmin represents an example of a 'moonlighting' protein that overcomes the one gene-one structure-one function concept to follow the changes of the organism in its physiological and pathological conditions. Graphical abstract: Image 1 Highlights: Ceruloplasmin (Cp) is a highly conserved and moonlighting protein with multifunctional activity. Cp is a multicopper oxidase evolved to insure a safe handling of oxygen in metabolic pathways. It serves as an indirect marker for selection against A. hydrophila resistance in rohu carp. Its role has been identified during development, pathogen attack and inflammatory response.